A Single-Layer Dual-Band Reflectarray Cell for 5G Communication Systems - Sandra Costanzo; Francesca Venneri; Antonio Borgia; Giuseppe Di Massa (International Journal of Antennas and Propagation)
A single-layer dual-band reflectarray cell is proposed in this work for future 5G systems. A reflectarray unit cell operating at 28/38 GHz is designed by adopting two pairs of miniaturized fractal patches, offering low losses (<0.7 dB) and almost full-phase ranges (≅320°) at both operating frequencies. The proposed configuration allows to achieve very small interelement spacings and negligible mutual coupling effects between the two bands, thus assuring an independent phase-tuning mechanism at both desired frequency bands. The designed compact cell is successfully adopted to demonstrate reflectarrays’ abilities in achieving fixed scanned-beam and/or multibeam patterns, under the dual-band operation mode. Full-wave numerical validations, performed on the synthesized reflectarray structures, confirm the effectiveness of the designed dual-band configuration in achieving independent radiation patterns and quite good bandwidths, at the two designed frequencies. Thanks to its compactness and versatility in achieving both frequency diversity and multibeam/scanned-beam radiation patterns, the proposed unit cell is appealing for future 5G applications.